Obstacles to the application of Islamic financing - the form of lease ending with ownership An applied study on Jumhouria Bank, Souk Al-Khamis branch, Imsihel (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study dealt with the obstacles to the application of the lease ending with ownership and its impact on the mechanism of applying the lease ending with ownership in which the bank operates, as well as the statement of the application of the lease ending with ownership on the banks’ revenues, and the aim of finding possible solutions to address the risks incurred by the bank through the application of the lease ending with ownership, (35) samples were distributed to the employees of Jumhouria Bank, Souk Al-Khamis Branch, Amsihel, and (31) questionnaire sheets were collected, and then the data was analyzed and processed using the statistical analysis program (spss) to dump and schedule the data and conduct the appropriate statistical analysis to choose hypotheses. One of the most important results was that the bank followed complex procedures when opening the application of the lease ending in ownership, which leads to the reluctance of customers to deal with the bank. One of the most important recommendations for the bank was to simplify the procedures when opening the lease ending with ownership application, in order to increase the number of customers in the bank and maintain the existing customers.
Keywords: obstacle; lease ending with ownership; bank revenues; bank profitability